A Series of Lectures Entitled “Lessons from Our Masters” and a Seminar on Teaching Methods in the Humanities - Julkowska, Violetta; Balbuza, Katarzyna (Sensus Historiae, 2026)
On March 17, 2026, the Faculty of History at Adam Mickiewicz University in Poznań launched a series of lectures under the collective title “Lessons from Our Masters.” The series focuses on reflections on the broadly understood academic teaching practices of historians from the former Faculty of Humanities, and later the Institute of History at the Faculty of History of Adam Mickiewicz University, in the context of contemporary educational practices.